One-pot nucleophilic substitution–double click reactions of biazides leading to functionalized bis(1,2,3-triazole) derivatives - Reissig, Hans-Ulrich; Yu, Fei (Beilstein Journal of Organic Chemistry, 2023)
The nucleophilic substitution of benzylic bromides with sodium azide was combined with a subsequent copper-catalyzed (3 + 2) cycloaddition with terminal alkynes. This one-pot process was developed with a simple model alkyne, but then applied to more complex alkynes bearing enantiopure 1,2-oxazinyl substituents. Hence, the precursor compounds 1,2-, 1,3- or 1,4-bis(bromomethyl)benzene furnished geometrically differing bis(1,2,3-triazole) derivatives. The use of tris[(1-benzyl-1H-1,2,3-triazol-4-yl)methyl]amine (TBTA) as ligand for the click step turned out to be very advantageous. The compounds with 1,2-oxazinyl end groups can potentially serve as precursors of divalent carbohydrate mimetics, but the reductive cleavage of the 1,2-oxazine rings to aminopyran moieties did not proceed cleanly with these compounds.
Keywords: alkynes; azides; copper catalysis; nucleophilic substitution; 1,2-oxazines